2011
DOI: 10.1074/jbc.m111.228023
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal Domain of the Yeast Mitochondrial RNA Polymerase Regulates Multiple Steps of Transcription

Abstract: Transcription of the yeast (Saccharomyces cerevisiae) mitochondrial (mt) genome is catalyzed by nuclear-encoded proteins that include the core RNA polymerase (RNAP) subunit Rpo41 and the transcription factor Mtf1. Rpo41 is homologous to the single-subunit bacteriophage T7/T3 RNAP. Its ϳ80-kDa C-terminal domain is highly conserved among mt RNAPs, but its ϳ50-kDa N-terminal domain (NTD) is less conserved and not present in T7/T3 RNAP. To understand the role of the NTD, we have biochemically characterized a serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 39 publications
(64 reference statements)
3
44
0
Order By: Relevance
“…The observed phenotypes, together with previously reported data obtained using large deletions in the N-terminal extension in vivo [33,44,45] and in vitro [46], also support the conclusion that this region of the protein is not involved in the main enzymatic activity.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The observed phenotypes, together with previously reported data obtained using large deletions in the N-terminal extension in vivo [33,44,45] and in vitro [46], also support the conclusion that this region of the protein is not involved in the main enzymatic activity.…”
Section: Discussionsupporting
confidence: 69%
“…Subsequent studies suggested that this domain couples transcription to RNA processing and translation through interactions with the Nam1 and Sls1 proteins [34,44,45]. Deletion of the first 270 amino acids of the Rpo41p NTE domain does not affect the catalytic activity of the polymerase in vitro, in fact enhancing the productive/abortive ratio of RNA synthesis, whereas a 380 aa deletion decreases initiation from duplex, but not premelted promoters [46]. …”
Section: Introductionmentioning
confidence: 99%
“…5B, lanes 6–10). The MTF1 dependent decrease in runoff transcription on pre-melted promoters has been observed previously and attributed to inhibition of promoter escape due to a too strong interaction with the melted promoter and MTF1(3, 14). It is relieved by deletions in the MtRNAP N-terminal domain that weaken the interaction with MTF1(3, 14).…”
Section: Resultssupporting
confidence: 56%
“…Oris, 14S, and COX II nucleotide sequences from the −20 to the +40 position (+1 indicated the first transcribed ribonucleotide) were cloned into puC19 and used as templates (Table 1S). Transcription at 14S and COX II promoters displays a well studied abortive transcription pattern from 2 to 10 nts Paratkar et al, 2011;Velazquez et al, 2012) and a run-off transcript of 65 and 66 nts respectively (Fig. 3, lanes 1 and 2).…”
Section: Oris Are Active Promoters With Reduced Transcription Efficiencymentioning
confidence: 95%